2003
DOI: 10.1089/104303403322611728
|View full text |Cite
|
Sign up to set email alerts
|

In VivoSelection of Human Hematopoietic Cells in a Xenograft Model Using Combined Pharmacologic and Genetic Manipulations

Abstract: Strategies that increase the ability of human hematopoietic stem and progenitor cells to repair alkylator-induced DNA damage may prevent the severe hematopoietic toxicity in patients with cancer undergoing high-dose alkylator therapy. In the context of genetic diseases, this approach may allow for selection of small numbers of cells that would not otherwise have a favorable growth advantage. No studies have tested this approach in vivo using human hematopoietic stem and progenitor cells. Human CD34(+) cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…37 The most intense studied genes for chemoprotective gene therapy are MDR1 [6][7][8][9][10] and MGMT. [24][25][26] As drug combinations are common in most chemotherapeutic regimens, gene therapy with a combination of several genes is particularly promising and would increase the therapeutic index of combination chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The most intense studied genes for chemoprotective gene therapy are MDR1 [6][7][8][9][10] and MGMT. [24][25][26] As drug combinations are common in most chemotherapeutic regimens, gene therapy with a combination of several genes is particularly promising and would increase the therapeutic index of combination chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Thus, gene transfer of MGMT P140K into hematopoietic stem cells opened a way to better exploit the therapeutic potential of combined treatment with O 6 -BG and alkylating agents. [21][22][23] This approach was already applied successfully in several in vivo investigations with mice 24,25 and in a canine model demonstrating that retroviral overexpression of MGMT P140K in blood stem cells prevented myelosuppression associated with combination of O 6 -BG and the alkylating agent temozolomide (TMZ). 26 As in clinical protocols usually drug combinations are used, simultaneous expression of two chemoprotective proteins with different mechanisms of action would be advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…This approach provides selective protection of hematopoietic cells at the same time sensitizing MGMT-expressing tumor cells to chemotherapy. [35][36][37][38][39] Such use of mutant MGMT vectors is currently underway in several cancer chemotherapy trials (S Gerson, personal communication; L Wagner, personal communication). In the current study, the detection of vector for prolonged periods of time in the majority of subjects suggest expression of wild-type MGMT protein was not immunogenic when administered in this setting and may serve as a baseline for monitoring future gene therapy studies using the mutant protein.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to potential use in generating chemoresistance, we and others have found that the combined use of 6-BG and MGMT mutants leads to effective in vivo selection of transduced stem cells, including human HSC in xenograft models [ 35,37,62,64 ]. This approach could have additional therapeutic applications in genetic diseases, as demonstrated in mouse models of thalassemia [ 65 ]; protoporphyria [ 66 ]; HIV therapy [ 67,68 ]; and graft modulation following allogeneic transplant.…”
Section: Engineering Chemoresistancementioning
confidence: 98%